2015
DOI: 10.1038/srep10276
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic squeezing for intracellular antigen loading in polyclonal B-cells as cellular vaccines

Abstract: B-cells are promising candidate autologous antigen-presenting cells (APCs) to prime antigen-specific T-cells both in vitro and in vivo. However to date, a significant barrier to utilizing B-cells as APCs is their low capacity for non-specific antigen uptake compared to “professional” APCs such as dendritic cells. Here we utilize a microfluidic device that employs many parallel channels to pass single cells through narrow constrictions in high throughput. This microscale “cell squeezing” process creates transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 60 publications
2
78
0
2
Order By: Relevance
“…Furthermore, this tool was used for quantifying cellular electrical properties since the deformed cells effectively seal constriction channel walls, and block electric lines, enabling single-cell electrical property characterization [53][54][55][56]. Meanwhile, the constriction channel design was also used as a tool to study chemical synthesis of red blood cells [57] or deliver vector-free gene vectors [42,58].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this tool was used for quantifying cellular electrical properties since the deformed cells effectively seal constriction channel walls, and block electric lines, enabling single-cell electrical property characterization [53][54][55][56]. Meanwhile, the constriction channel design was also used as a tool to study chemical synthesis of red blood cells [57] or deliver vector-free gene vectors [42,58].…”
Section: Discussionmentioning
confidence: 99%
“…A promising approach of antigen delivery to B cells is via the targeting of antigens to CD19 [84]. Szeto et al [85] recently reported another interesting approach using a microfluidic device for antigen delivery to B cells through a process termed mechanoporation. In this microfluidic device, B cells are passed through narrow channels.…”
Section: Clinical Application Of B Cell-based Cancer Vaccinesmentioning
confidence: 99%
“…The microfluidic device has demonstrated applicability in delivering a variety of materials with a wide range of sizes that are retained by the cells, allowing for the manipulation of their biological properties . Here, our use of in vitro CTC models and clinical PDAC patient samples has demonstrated the additional utility of this platform to selectively deliver payload within a heterogeneous population of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of a wide range of cargo sizes (3 kDa to 2 MDa) can be achieved with high efficiency and uniform distributions, suggesting that the size of holes resulting from the membrane disruption are homogeneous within that population of cells . While this transient disruption of the cell membrane allows for bidirectional movement of material across the membrane, cells remain viable and retain their proliferative capacity and biological activity . Here we demonstrate the use of a microfluidic system to confer selective cytosolic delivery within a mixture of cells based on cell size.…”
Section: Introductionmentioning
confidence: 93%